Cutaneous and Subcutaneous Metastases From Atypical Laryngeal Carcinoids: Case Report and Review of the Literature. Issue 7 (February 2016) - Wang, Kui-Rong; Jia, Yuan-Jing; Zhou, Shui-Hong; Wang, Qin-Ying; Bao, Yang-Yang; Feng, Zhi-Ying; Yao, Hong-Tian; Fan, Jun
Abstract : Abstract: The incidence of cutaneous and subcutaneous metastases from atypical laryngeal carcinoids is approximately 20%. However, the pathogenesis and natural history of, and prognostic factors for, the condition remain poorly understood. We reported a 54-year-old female presented with cutaneous and subcutaneous metastases from atypical laryngeal carcinoid. Laryngoscopy revealed a 0.5 × 1.5-cm reddish mass on the laryngeal surface of the epiglottis. Under general anesthesia, a biopsy sample was obtained via suspension laryngoscopy. Routine pathology revealed atypical laryngeal carcinoid. Immunohistochemical staining of the sections of primary tumor was positive for cytokeratin, chromogranin A, synaptophysin, hypoxia-inducible factor-1α, P53, and CD56. GLUT-1, p-Akt, and PI3K were negative. The Ki-67 index was 15%. Supraglottic laryngectomy and selective right-neck dissection were performed. After 6 months, the patient complained of pain in the right wall of the chest; multiple cutaneous and subcutaneous nodules were evident at that site and in the abdomen. An abdominal nodule was biopsied and pathology revealed that the atypical metastatic carcinoid had metastasized to both cutaneous and subcutaneous areas of the abdomen. Chemotherapy was then prescribed. Currently, the intrathecal drug delivery system remains in place. No local recurrence has been detected. Furthermore, we systematically reviewed clinical manifestations of the disease, pathogenesis, prognostic factors, and treatment. The metastasis rate (cutaneous and subcutaneous) was approximately 12.2%. Thirty patients (62.5%) with cutaneous and subcutaneous metastases exhibited contemporaneous lymph node invasion. The 3-, 5-, and 10-year survival rates were 44.0%, 22.0%, and 13.0%, respectively. The prognosis of patients with atypical laryngeal carcinoids was poor. Relevant prognostic factors included the level of p53, human papilloma virus status, certain hypoxic markers, and distant metastasis. No optimal treatment for such metastases has yet been defined.